Fronteras entonativas en discursos de Tenerife - Toledo, Guillermo Andres (2010)
Guillermo Toledo, "Fronteras entonativas en discursos en Tenerife" The intermediate intonational phrases and the major intonational phrases are analyzed in Spanish broadcasting discourses. The three female informants are from Tenerife: a broadcaster, a journalist and a newsreader. In the intermediate phrases the primary and secondary phonological association are observed taken place in oxytone and paroxytone words. In oxytones the pitch accents show a primary association of the tone with the accented syllable. This accented syllable becomes imbedded in the phrasal accent by secondary association, it results always high. In paroxytones a primary phonological association occurs between the tone and the accented syllable, this syllable appears as low, but by means of an secondary phonological association between the tone and the phrasal accent, the syllable recovers its higher prominence. The final intonational phrases induce low nuclear accents. In this way, it suggests a pragmatic contrast of intermediate phrases cued by continuation rise contours, (the discourse continuity) opposed to the  final phrases marked by  low contours, (the discourse conclusion).   Key words : Autosegmental and Metrical Phonology, Spanish Phrasing, Primary and Secondary Phonological Association, Intonational Meaning and Discourse.